HUBUNGAN COPING STRES TERHADAP KUALITAS HIDUP PENDERITA SKIZOFRENIA PADA MASA REMISI SIMPTOM - Stefani Ivana; Devi Jatmika (Universitas Bunda Mulia, 2017)
Schizophrenia is a mental disorder characterized by the appearance of symptoms such as hallucinations and delusions. The decrease in the frequency and intensity of symptoms is also called the period of symptom remision. Excessive unresolved stress conditions associated with recurrence / reappearance of schizophrenia symptoms. Relapse can affect the quality of life in people with schizophrenia during remission of symptoms.The purpose of this study was to determine the relationship between stress coping with quality of life in people with schizophrenia period remission symptom. This research is a quantitative study with correlational approach. The design of this study used is cross sectional. This study enrolled 52 people with schizophrenia disorder during the remission of symptoms. The data were collected using an adapted questionnaire, the SQLS (Self-Report Quality of Life measure for people with Schizophrenia) and the COPE Brief. Data analysis was done by using Pearson correlation statistic technique. The results showed that there was no correlation between stress coping and quality of life in schizophrenic patients on remission of symptom (p = 0,765, p> 0,05). There is no relationship between coping stress and quality of life caused by many other factors that affect the quality of life, namely negative stigma, self-mastery, family support, socioeconomic, treatment factors. Keywords: coping stress, quality of life, schizophrenia